John Bell interviewed by Hazel de Berg in the Hazel de Berg collection (1973) - Bell, John, 1940-; De Berg, Hazel, 1913-1984. (1973)
Bell, actor, director and co-founder of the Nimrod Street Theatre in Sydney speaks of his work at the Nimrod ; his acting career ; the emergence of Australian drama ; playing Hamlet ; how he prepares for a role ; his reasons for staying in the theatre.
Digital master available
Transcript available (22 p.)
Keywords: Bell, John, -- 1940- -- Interviews; Nimrod Theatre Company -- History; Actors -- Australia -- Interviews; Theatrical producers and directors -- Australia -- Interviews